We define 3 sequences $(a_n),(b_n),(c_n)$ with positive terms so that $$ a_{n+1}\leq\frac{b_n+c_n}{3}\ ,\ b_{n+1}\leq\dfrac{a_n+c_n}{3}\ ,\ c_{n+1}\leq\dfrac{a_n+b_n}{3} $$ Check if any of $(a_n),(b_n),(c_n)$ converge, and if they do find their limit.


My part of the proof is this: By adding the above inequalities we get $$ a_{n+1}+b_{n+1}+c_{n+1}\leq\frac{2}{3}(a_n+b_n+c_n) $$ We define the sequence $ (x_n) $ with $ x_n=a_n+b_n+c_n $ so we have $$ x_{n+1}\leq\frac{2}{3}x_n\Rightarrow \frac{x_{n+1}}{x_n}\leq\frac{2}{3}<1 $$ which implies that $ (x_n) $ is decreasing. We also have $ x_n>0, \forall n $ thus it's bounded, and so it converges to $ 0 $. Is it correct to say that since $ a_n<x_n $ then $ a_n\to0 $?


I forgot to mention that we also prove that $x_n\to0$.

  • 1
    $\begingroup$ $1+1/n$ is decreasing and bounded, but do not converges to $0$ $\endgroup$ – enzotib Jun 17 '17 at 12:04

Yes because you have the "sandwiched" inequality $0 < a_{n} < x_{n} \rightarrow 0$, so $a_{n} \rightarrow 0$.

EDIT: Of course, you have to make sure that $x_n \rightarrow 0$ in the first place, but you have that it is bounded by a geometric sequence which converges to zero which implies the stated convergence.

  • $\begingroup$ You mean $\leq $. $\endgroup$ – Displayname Jun 17 '17 at 12:06
  • $\begingroup$ Not necessarily since $a_n$, $b_n$ and $c_n$ are assumed positive. But $\leq$ would of course also be enough, however, this way I think the difference between "converging to zero" and "being zero" becomes a bit clearer. $\endgroup$ – Andre Jun 17 '17 at 13:34
  • $\begingroup$ No, it is not equivalent to this. Take for example the case $0 < \frac{1}{n} < \frac{2}{n}$. All the inequalities are strict for every $n$, but both converge to 0 as $n \rightarrow \infty$. $\endgroup$ – Andre Jun 18 '17 at 0:45
  • $\begingroup$ That is not what you wrote. You are taking the limit since you used a $\rightarrow $. $\endgroup$ – Displayname Jun 18 '17 at 5:49
  • $\begingroup$ Your current statement literally is $ 0 < a_n < 0$. $\endgroup$ – Displayname Jun 18 '17 at 6:02

To prove that $x_n$ converges to $0$ you need to take the limit $$ 0\leq x_{n+1}\leq \frac{2}{3}x_n \implies 0\leq l\leq \frac{2}{3}l \implies l=0 $$


Since $\{x_n\}$ is decreasing and bounded from below, it is convergent. But this does not guarantee that the limit is zero. Indeed, since

$$0< x_{n+1}\le\frac{2}{3}x_n$$

we have

$$0< x_n\le\left(\frac{2}{3}\right)^{n-1}x_1$$

This implies that $x_n\to0$ as $n\to\infty$.

We have $\displaystyle 0<a_n<\frac{1}{3}x_n$, $\displaystyle 0<b_n<\frac{1}{3}x_n$ and $\displaystyle 0<c_n<\frac{1}{3}x_n$.

So $a_n\to 0$, $b_n\to 0$ and $c_n\to 0$ as $n\to\infty$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.